Análise do desempenho acadêmico dos estudantes da EPPEN - Santos, Andreia Trinca Dos [UNIFESP] (2019)
The educational social policies implemented since the 21st century have allowed the excluded sections of the population to have equal conditions for access and permanence to higher education. The creation of a reserve of vacancies for students coming from public education in the Federal Institutions of Higher Education brought significant changes at the Universidade Federal de São Paulo (Unifesp).Thus, the objective of this study is to verify if, at the end and during the course, the academic performance of the quota students and the non-quota students is equivalent in the undergraduate courses of the Escola Paulista de Política, Economia e Negócios (EPPEN) of Unifesp. In order to achieve this objective, a documentary analysis of the terms of adhesion of Unifesp to the Sistema de Seleção Unificado (SiSU) was carried out, obtained information from the Pró-reitoria de Graduação (Prograd) and statistical analyzes based on the Coeficiente de Rendimento (CR) of the students who joined EPPEN in 2013 and 2014.The relevance of this study is justified by the recent changes in the profile of the students in the federal higher education network. The methodological definitions used define the approach of the study as quantitative with the use of the case study method and the quantitative data comparison technique. In order to conduct the study, six propositions were drawn up in order to outline the profile of EPPEN students in several aspects, with three subdivisions: formed, ongoing and dropping out. In order to highlight the proposed comparison, statistical models were developed through multivariate data analysis techniques using the IBM-SPSS software. The results show that the majority of the students entered the EPPEN by the wide competition, with ages between 17 and 19 years, studied in private school and is female. There is a 34.25% evasion rate. Of the 613 enrollees in the 78 period they completed their studies, most of them female. It was also verified the inexistence of significant differences between the academic performance of quota and non-quota students, and those who studied in public and private schools, thus, it is concluded that the similarity in performance corroborates the importance of quota policy as a tool to combat social inequalities.